Hsp90-peptide complexes stimulate antigen presentation through the class II pathway after binding scavenger receptor SREC-I - Murshid, Ayesha (Immunobiology, 2014)
Molecular chaperones such as heat shock protein 90 (Hsp90) have been shown to form complexes with tumor antigens and can be used to prepare anticancer vaccines largely due to this property. Earlier studies had suggested that, mice immunized with a molecular chaperone based vaccine derived from tumors became immune to further vaccination and that both CD8(+) and CD4(+) T cells were activated by the chaperone vaccine in a manner dependent on scavenger receptor SREC-I. Here we have investigated mechanisms whereby SREC-I might facilitate uptake of Hsp90 conjugated peptides by APC into the MHC class II pathway for presentation to CD4(+) T cells. Our studies showed that antigenic peptides associated with Hsp90 were taken up into the Class II pathway by a mechanism dependent on SREC-I binding and internalization and presented to CD4(+) T cells. In addition our studies showed that SREC-I could associate with MHC class II molecules on the cell surface and in intracellular endosomes, suggesting a mechanism involving facilitated uptake of peptides into the MHC class II pathway. These studies in addition to our earlier findings showed SREC-I to play a primary role in chaperone-associated antigen uptake both through cross priming of MHC class I molecules and entry into the class II pathway.